Downlink transmit beamforming in TDD-MIMO systems - XU Dao-feng 1; YANG Lv-xi1 (Tongxin xuebao)
Concerning the access terminals （AT） use single antenna to transmit, two precoding methods were proposed for TDD systems that combined instantaneous CSI and statistical CSI effectively. When without feedback, instant perfect CSI was utilized to the most, while using the degrees of freedom to guarantee the average throughput of other streams; when with limited feedback, the direction of the channel vector corresponding to the second antenna at AT was firstly estimated using constrained maximum likelihood estimation, and then the optimal precoding matrix was determined through singular value decomposition of the estimated channel matrix. Simulations demonstrate the effectiveness of the proposed methods.